Kompetensi Konselor Sebagai Guru Pendamping Bagi ABK dalam Pendidikan Inklusif - Putri Nabila Azaria; Nandang Budiman; Nadia Aulia Nadhirah (Universitas Sebelas Maret, 2025)
In an effort to help ABK to develop their abilities he has, special services can be provided. This is done in the hope of helping ABK overcome and resolve the obstacles encountered. Therefore, the role of counselors is also needed as part of the accompanying teacher for the ABK. However, when going to handle ABK there are some counselor competencies that are important to be considered and mastered. This study aims to analyze the role and competencies of counselors that must be mastered by the counselor against ABK. The study was conducted by the Sysmatic Literature Review method through steps to formulate problems, find literature, evaluate data, and analyze and interpret the raised problems. After conducting a literature review, it was found that the role of counselors can greatly assist ABK in overcoming its obstacles and it is very important to pay attention and have competencies when doing counseling services, especially with ABK.